If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.21y + -2.6 = 0.11y + 1 + -0.8y Reorder the terms: -2.6 + 0.21y = 0.11y + 1 + -0.8y Reorder the terms: -2.6 + 0.21y = 1 + 0.11y + -0.8y Combine like terms: 0.11y + -0.8y = -0.69y -2.6 + 0.21y = 1 + -0.69y Solving -2.6 + 0.21y = 1 + -0.69y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '0.69y' to each side of the equation. -2.6 + 0.21y + 0.69y = 1 + -0.69y + 0.69y Combine like terms: 0.21y + 0.69y = 0.9y -2.6 + 0.9y = 1 + -0.69y + 0.69y Combine like terms: -0.69y + 0.69y = 0.00 -2.6 + 0.9y = 1 + 0.00 -2.6 + 0.9y = 1 Add '2.6' to each side of the equation. -2.6 + 2.6 + 0.9y = 1 + 2.6 Combine like terms: -2.6 + 2.6 = 0.0 0.0 + 0.9y = 1 + 2.6 0.9y = 1 + 2.6 Combine like terms: 1 + 2.6 = 3.6 0.9y = 3.6 Divide each side by '0.9'. y = 4 Simplifying y = 4
| 4x^2+36x-44=0 | | 3z-25=-65+8z | | n^2+49n-498=0 | | -8-12x=52+8x | | 4x^2+36x-14=0 | | 3a-4b-c=12 | | 4(n+2)=6n+4 | | x^2-6.5x+42=0 | | 3t-4=t-8 | | 6729-3465= | | 1627+4738= | | xyz=100 | | xyz=80 | | 26-0.25Q=2+0.5Q | | 6x^3-18x^2+24=0 | | -6x(6x^2-6x+9)= | | (3x^3-4x^2+9)-(9-4x^2+3x^3)= | | 4t-5=7t+1 | | 2x+y=126 | | sin(7x)+-1sin(3x)=0 | | e^2-3x=12 | | x+7(3x+4)=11 | | y=-5+7x+x^2 | | 2+1-20= | | 2-2p-15= | | 2-16+63= | | 2+1+6= | | 2-4k-60= | | ax^2-4x+3a+1=0 | | 2-9b+14= | | 2-8p+40= | | 2+9r+16= |